Anaphora: Analysis, Algorithms and Applications [electronic resources]: 6th Discourse Anaphora and Anaphor Resolution Colloquium, DAARC 2007, Lagos, Portugal, March 29-30, 2007. Selected Papers - Discourse Anaphora and Anaphor Resolution Colloquium (6th : 2007 : Lagos, Portugal); Branco, Antonio (Berlin, Heidelberg : Springer-Verlag Berlin Heidelberg, 2007)
34